Public trust in government : Case study in Kota Kinabalu... [et al.] - Richard, Charissa G; Hamzah, Farah Ashikin (2014)
The research explains on the indicator of the government performances to determine the level of public trust in government in the City of Kota Kinabalu. The research is based on a quantitative method as distribute the questionnaires was taken as the subject of justification. The quantitative method was used to confirm the findings quantitatively. Among the indicator of the government performances to measure the level of public trust in government are public service delivery, the use of E - Government, and integrity which constructed by the researchers. These three indicators will be used to determine the level of public trust in government. As qualitative measures, researchers will analyze the findings from the findings from other researchers as well to see the alignment of public trust in government. Government performances is used to be the benchmark of the public trust as it's managed to fulfill its level of the public trust as well as to represent the government performances. The findings determine the level of public trust in government. The association between government performance and public trust will be discussed and used for the purpose of recommendation on the public trust in government.